2017
DOI: 10.6004/jnccn.2017.0061
|View full text |Cite
|
Sign up to set email alerts
|

Are We on the Same Page? Patient and Provider Perceptions About Exercise in Cancer Care: A Focus Group Study

Abstract: Physical activity (PA) during and after cancer treatment can help with symptom management and reduce the risk of cancer recurrence. However, it is unclear what constitutes an optimal exercise program. In addition, provider and patient barriers exist to the recommendation and adoption of exercise as part of a cancer treatment plan. The goal of this study was to determine how providers and patients feel about exercise during cancer treatment and explore what the barriers to implementing such a program might be. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
62
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(63 citation statements)
references
References 12 publications
1
62
0
Order By: Relevance
“…A recent survey of 971 oncology clinicians that was conducted by the American Society of Clinical Oncology indicated that 78.9% of respondents agreed that oncology clinicians should recommend physical activity to their patients . Observed barriers to clinicians referring patients to exercise programming include lack of awareness of the potential value of exercise in cancer populations, uncertainty regarding the safety or suitability of exercise for a particular patient, lack of awareness regarding available programs to help facilitate exercise in cancer populations, need for education and skills development for making referrals, and a belief that referrals to exercise programming are not within the scope of practice for oncology clinicians …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent survey of 971 oncology clinicians that was conducted by the American Society of Clinical Oncology indicated that 78.9% of respondents agreed that oncology clinicians should recommend physical activity to their patients . Observed barriers to clinicians referring patients to exercise programming include lack of awareness of the potential value of exercise in cancer populations, uncertainty regarding the safety or suitability of exercise for a particular patient, lack of awareness regarding available programs to help facilitate exercise in cancer populations, need for education and skills development for making referrals, and a belief that referrals to exercise programming are not within the scope of practice for oncology clinicians …”
Section: Introductionmentioning
confidence: 99%
“…23 Observed barriers to clinicians referring patients to exercise programming include lack of awareness of the potential value of exercise in cancer populations, uncertainty regarding the safety or suitability of exercise for a particular patient, lack of awareness regarding available programs to help facilitate exercise in cancer populations, need for education and skills development for making referrals, and a belief that referrals to exercise programming are not within the scope of practice for oncology clinicians. 21,22,[24][25][26] In summary, the scientific evidence base supports exercise, and patients and clinicians generally agree that patients should be moving throughout their cancer therapy and survivorship. Translating from the current state to exercise assessment, advice, referral, and engagement as standard practice for all people living with and beyond cancer is a multifactorial puzzle to be solved.…”
Section: Introductionmentioning
confidence: 99%
“…Models of care that provide access to exercise and rehabilitation professionals have been developed but are not used broadly and the workforce supporting them is still developing [9]. As a result, exercise prescription frequently is overlooked in cancer care planning [10,11]. Although recommendations have urged greater integration of exercise into the cancer care continuum, active integration will require more precise guidelines to support provider decision making [12].…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] To advance our understanding of exercise accessibility, participation, and effectiveness as a clinical tool in oncology, research in "real-world" settings using evidence-based and sustainable approaches are needed. 9 Moreover, routine monitoring of exercise programing has been shown to support sustained behavior change. Recent reviews suggest that home-based exercise that is coordinated and supported by qualified exercise professionals (QEPs) at a cancer center are a preference for a majority of cancer survivors.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 This preference may largely be because of convenience 7 and confidence in the qualifications and experience that accompanies guidance and support from QEPs at a Cancer October 1, 2019 cancer center. 9 Moreover, routine monitoring of exercise programing has been shown to support sustained behavior change. 10 Accordingly, a cancer center-based program with at-home or independent, unsupervised exercise prescriptions and routine follow-up may be a viable and preferential delivery model in people with cancer that are further enhanced by: 1) internal referral connections between oncology-directed care and QEPs, 2) feedback on patient outcomes embedded within a clinical record that can be expeditiously reported to the medical team, and 3) lower requirement for infrastructure and personnel for program delivery compared with one-on-one exercise programing.…”
Section: Introductionmentioning
confidence: 99%